2020
DOI: 10.1002/pssa.201900892
|View full text |Cite
|
Sign up to set email alerts
|

Halide Vapor Phase Epitaxy α‐ and ε‐Ga2O3 Epitaxial Films Grown on Patterned Sapphire Substrates

Abstract: The growth of Ga2O3 films by halide vapor phase epitaxy on plain and cone‐shaped patterned sapphire substrates (PSS) is reported. The obtained specimens are characterized by X‐ray diffraction, transmission electron microscopy, cathodoluminescence, optical transmission spectroscopy, and current–voltage measurements. Both types of Ga2O3 layers are of reasonably high crystal qualities; their physical properties, however, are very different. Under the same conditions, the growth on plain substrates results in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 26 publications
0
27
0
2
Order By: Relevance
“…We assumed that the -phase was grown at the top and bottom of the CF-PSS, and the "-phase was grown on the sidewall of the CF-PSS. In a previous report, Shapenkov et al (2020) confirmed that an -Ga 2 O 3 epilayer was grown on the top of the pattern, and an "-Ga 2 O 3 epilayer was grown on the sidewall of the pattern. The 004 diffraction peak position of the -Ga 2 O 3 epilayer was observed at 38.85 (JCPDS No.…”
Section: Resultsmentioning
confidence: 55%
“…We assumed that the -phase was grown at the top and bottom of the CF-PSS, and the "-phase was grown on the sidewall of the CF-PSS. In a previous report, Shapenkov et al (2020) confirmed that an -Ga 2 O 3 epilayer was grown on the top of the pattern, and an "-Ga 2 O 3 epilayer was grown on the sidewall of the pattern. The 004 diffraction peak position of the -Ga 2 O 3 epilayer was observed at 38.85 (JCPDS No.…”
Section: Resultsmentioning
confidence: 55%
“…The articles raising the most attention in the form of citations within the year of appearance 2020 are listed below. [ 1–6 ]…”
Section: Figurementioning
confidence: 99%
“…Достигнут значительный прогресс в выращивании эпитаксиальных пленок [1][2][3][4][5][6][7][8][9]. Корундообразная α-фаза обладает среди всех политипов оксида галлия наибольшей шириной запрещенной зоны E g , не менее 5.3 эВ, и при легировании Sn или Si имеет высокую донорную проводимость [3,8,[10][11][12][13][14][15]. В то же время ε-фаза с E g , близкой к 4.9 эВ [1,2,16], является второй после β-Ga 2 O 3 по температурной стабильности.…”
Section: Introductionunclassified